Deposition of ambient ultrafine particles in the respiratory tract of children: A novel experimental method and its application. (January 2020) - Guo, Lingli; Johnson, Graham R.; Hofmann, Werner; Wang, Hao; Morawska, Lidia
Abstract: Because of ethical and practical constraints, there are few experimental studies on the deposition of ultrafine particles (<100 nm; UFPs) in the respiratory tract of children. To address this deficiency, we developed a novel method based on a flow-through chamber bag inhalation system, which is capable of measuring in situ size-resolved and total deposition of ambient UFP in a large number of children. The method was validated on four children (aged 9–11 years) at an urban primary school in Brisbane, Australia with breathing frequency ranging from 12 to 28 breaths/min, with repeated measurements conducted for a reference adult on 4 different days to test its repeatability. A stochastic lung deposition model (IDEAL) was used to predict total particle deposition to further asses the performance of the method. The total deposition fraction was 0.59 ± 0.02 (Mean ± SD) in 4 experiments of the reference adult, while it was 0.59 ± 0.13 in 4 children and in good agreement with the model calculated value of 0.57 ± 0.09. The method was repeatable (with precision ranging from 0.01 to 0.06) and sensitive enough to reflect the influence of breathing patterns on size resolve deposition fraction and the impact of particle size distribution on total deposition. Three measurements of size-resolved (10–379 nm) and total deposition fraction can be finished in 15 min (with the exposure time of only half of this), even at concentrations as low as 1.7 × 10 3 cm −3 . We demonstrated that the novel method is capable of providing fast and reliable quantification of size-resolved and total deposition of UFP in respiratory tracts of children and adults. Highlights: A new flow-through method was developed to measure size resolved and total deposition of ultrafine particles in children. The method was validated by measurements and modelling of four children and one adult at a primary school. Deposition fractions due to varying breathing pattern and particle size distribution can be differentiated by the method. This method is applicable to other settings for human deposition measurement of ultrafine particles.